Dietary non-compliance among Indonesian patients with diabetes and kidney disease: A focus on risk-associated eating behaviors - Ismi Irfiyanti Fachruddin; Andi Hardianti (AcTion: Aceh Nutrition Journal, 2025)
Chronic illnesses, such as diabetes mellitus (DM), hypertension, and chronic kidney disease (CKD), are increasingly prevalent in Indonesia, partly due to poor dietary habits. This study aimed to analyze the association between risky food consumption and the occurrence of hypertension and CKD in individuals with diabetes and to explore the factors influencing unhealthy food choices. This cross-sectional study used data from the 2023 Indonesian Health Survey. The analysis included 14,935 adults diagnosed with diabetes mellitus, of whom 143 were identified as having both hypertension and CKD. Stratified random sampling was applied based on census blocks. Data were collected through structured interviews and health assessments of dietary patterns and a history of chronic illness. Chi-square tests and logistic regression were performed to assess the associations, with p < 0.05 considered significant. Hypertension was significantly associated with CKD (OR, 2.16; 95% CI: 1.68–2.77; p < 0.001). Risky dietary patterns, particularly high intakes of salty foods, processed meats, and sugary beverages, were significantly associated with hypertension. The major drivers of unhealthy food consumption include taste, affordability, and lack of health awareness. Risky food intake contributes to hypertension and CKD in patients with diabetes. Targeted public health interventions are required to improve dietary behavior and raise awareness.